Evaluation of a simple alkaline pretreatment for screening of sugarcane hybrids according to their in vitro digestibility - Masarin, Fernando [UNESP]; Neves, Aline S.; Milagres, Adriane M. F.; Ferraz, Andre (Elsevier B.V., 2013)
Lignin depletion in new cultivars or transgenic plants has been identified as a way to diminish the recalcitrance of lignocellulosic materials. Direct enzymatic digestion of these materials provides some discrimination concerning their digestibility, but the cellulose conversion to glucose is usually lower than 30% in the case of sugarcane bagasse. This study evaluates the alkaline pretreatment of eleven sugarcane hybrids and one reference sample as a method for enhancing sample digestibility with the aim of better discrimination among cultivars. The treatment of the bagasse samples with 0.1% NaOH solutions resulted in an average of 10% of dry mass solubilization, with significant variation among the samples. The mass balances for these treatments showed that the cellulose fraction remained almost unchanged, whereas the hemicellulose decreased in most of the samples. The lignin fraction decreased only in the plants that contained the highest initial lignin contents. Alkali-treated samples provided enhanced cellulose conversion levels, varying from 23% to 48% after 72 h of enzymatic digestion. After pretreatment, the samples were better distinguished according to their digestibility by enzymes. In general, the experimental hybrids with originally low lignin contents presented the highest digestibility. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Sugarcane; Lignin-depleted plants; Recalcitrance; Cellulases; Alkali pretreatment; Digestibility